Nyai Mahmudah Ahmad's Leadership in Islamic Boarding School Devlopment - Lailatul Usriyah; Ali Makrus; Zaimuariffudin Shukri Nordin (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
The figure of Nyai Mahmudah Ahmad can answer the skewed perspective regarding women as leaders. Nyai can become caregivers and have full expertise in Islamic boarding school development. Nyai was able to take her Islamic boarding school through the rapid currents of change and modernization. The aims of this research are: to describe Nyai's leadership role as an influencer and to describe her leadership role as a policy maker. This research uses a qualitative research approach, with a case study type and phenomenological design. Data analysis uses interactive descriptive with the Miles Huberman and Saldana model. The findings of this research are that Nyai's leadership role is: 1) As an influencer in the development of Islamic boarding schools, carried out by: (a) example, (b) faith in the field of religion (kitab kuning), (c) transformative leadership, (d) strength spiritual. 2) As a policy maker, referring to: (a) deliberation basis, (b) tabayyun basis, (c) rationality and intuitive basis